A pilot and feasibility study to assess children's consumption in quick-service restaurants using plate waste methodology. - Cohen, Juliana F.; Roberts, Susan B.; Anzman-Frasca, Stephanie.; Gamache, Madeleine M.; Lynskey, Vanessa M.; Matthews, Emilia.; Mueller, Megan P.; Sharma, Shanti.; Economos, Christina D. (2017)
Background: Children regularly consume foods from quick-service restaurants (QSR), but little is known about the foods that children order, the calories and nutrients consumed, the accuracy of stated calorie information, or the ability to assess food orders and consumption in QSRs. This study evaluated the feasibility of plate waste collection in QSRs and examined children's orders and consumption of meals from the standard and children's menus. Additional aims were to examine if the meals ordered met healthier standards for children's menu items and determine the accuracy of the QSR-stated energy content of foods.; Keywords: Quick-service restaurants, Child diet, Plate-waste, Bomb calorimetry, Dietary assessment, Fast food, Feasibility.; Springer Open.